The evolution of the term „Moral Person” in the Canonical Legal Order - DIERŻON, GINTER (Prawo Kanoniczne, 2014)
The author of the presented article focused his attention on the question of the evolution of the term “moral person” in the canonical legal order. The analyses he carried out show that in the Code of 1917 the term “moral person” was dominant and equivalent to the term “juridical person”. However, the commentators of the Code of 1917 pointed out that the notion did not suit other notions functioning in the secular law. Therefore, present codification uses the term “juridical person” while the term “moral person” refers only to the Catholic Church and the Apostolic See (can. 113 § 1 CL). In his considerations, the author proved that the notion “moral person” originates from the conviction that the source of all subjects mentioned in can. 113 § 1 CL is Divine law but also from the belief that hierarchically these subjects are superior to other subjects functioning in the canonical legal order. The author believes that the regulation included in can. 113 § 1 CL is of apologetic nature. By introducing this kind of declaration, the ecclesiastical legislator intends to protect the independence of the Catholic Church and the Apostolic See from the secular law. This type of subjectivity is also reflected in the inter-ecclesiastical field. On the one hand, it equips the Church with the ruling power, but it also gives other subjects a legal status in the inter-ecclesiastical area.